If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying F(x) = f(-1x) Multiply F * x xF = f(-1x) Remove parenthesis around (-1x) xF = f * -1x Reorder the terms for easier multiplication: xF = -1f * x Multiply f * x xF = -1fx Solving xF = -1fx Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'fx' to each side of the equation. fx + xF = -1fx + fx Combine like terms: -1fx + fx = 0 fx + xF = 0 Factor out the Greatest Common Factor (GCF), 'x'. x(f + F) = 0Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(f + F)' equal to zero and attempt to solve: Simplifying f + F = 0 Reorder the terms: F + f = 0 Solving F + f = 0 Move all terms containing x to the left, all other terms to the right. Add '-1F' to each side of the equation. F + -1F + f = 0 + -1F Combine like terms: F + -1F = 0 0 + f = 0 + -1F f = 0 + -1F Remove the zero: f = -1F Add '-1f' to each side of the equation. f + -1f = -1F + -1f Combine like terms: f + -1f = 0 0 = -1F + -1f Simplifying 0 = -1F + -1f The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Solution
x = {0}
| 15x-27=-6x-20 | | 6x-8=74 | | m-3=28 | | -23=5x-3 | | m-3=75 | | 1x-8=24x-22 | | -6x+3y+15x-8= | | 7y-2(3y-7)=18 | | -25x-30=-23x-14 | | 91=4v+15 | | -4x-3(3x-4)=40-6x | | X+88=x | | -22x-5=-6x+20 | | 2(x-7)+3x=21 | | 30=s/6 | | 9.46=5.6y-9.9y | | 3x-4=13x-85 | | 19-x=-8(x-5) | | 2x+3x+50= | | f(2)=-6x-3 | | 15.6+x=4.4 | | 5x-3x=1-10x | | 75/3=m | | -3x-12-2=-2x+10 | | 4+14x=x | | 38x2/4 | | 9x-45=3x+25 | | x^3-x^2-6x+8=0 | | y-14=20 | | 9(6x+7)=0 | | f(x)=2x^3+5x^2-6x-4 | | 5(3a+2b)+5(4a+4b)= |